Obstetric Renal Failure: Causes, Prognosis, and Evolution - H, Tchich; K, Harmak; I, Al-Firdaous; G, Medkouri; N, Mtioui; SS, Khayat; M, Zamd; M, Benghanem (Journal of Clinical Nephrology, 2024)
The incidence of obstetric acute renal failure remains significant in developing countries. The aim of our study is to define the risk factors involved in the occurrence of ARF during pregnancy or during the immediate postpartum period and to evaluate its evolutionary profile in terms of epidemiology, etiopathogenesis, and therapeutic management over the years in Morocco. This is a retrospective study conducted in the maternal-infant resuscitation service of the Ibn Rochd University Hospital of Casablanca, over the period from January 2020 to August 2023, including 95 patients. The current incidence in our series over this period was 22.2%. The mean age of our population was 33 ± 7.74 years [18-43 years], 67.3% of patients were in the gestational period, compared to 33.7% in the immediate postpartum period. Fourteen patients were primiparous (8.6%), 27.4% had a history of miscarriage, and 10.7% had a history of pre-eclampsia. Oligo-anuria was initially identified in 24 patients. The most frequent etiology was pre-eclampsia (56.7%), followed by hemorrhage (27%) and sepsis (19.3%). The evolution was marked by recourse to hemodialysis in 62% of cases, with a maternal mortality of 26%. The existence of heart disease, the context of pre-eclampsia, and the use of diuretics and vasoactive drugs were significantly correlated with maternal survival. No factor was correlated with secondary recovery from ARF. The development of health structures and the optimization of screening strategies are the keywords for prevention.